Post-fire change in structure and composition of the tree stratum and fuel load in a Pinus douglasiana forest in Mexico - Quintero-Gradilla, Shatya Devi; Jardel-Peláez, Enrique José; Cuevas-Guzmán, Ramón; García-Oliva, Felipe; Martínez-Yrizar, Angelina (Instituto de Ecología, A.C., 2019)
In pine forests with an historical fire regime of frequent low severity surface fires, under extreme weather conditions or a consequence of fire suppression, the severity of fires may increase. Response of vegetation to severe fire events was studied in a chronosequence of 8 years, 28 years and 60 years in a forest dominated by Pinus douglasiana in Mexico. Tree density (> 2.5 cm diameter) reached values of 1095 stems ha-1 ± 609 stems ha-1 and a basal area of 10.0 m2 ha-1 ± 2.2 m2 ha-1 in the 8 years stands; 28 years after stand-replacement fires, basal area (44.6 m2 ha-1 ± 3.0 m2 ha-1) was close to that of 60-year-old stands (49.0 m2 ha-1 ± 6.4 m2 ha-1). Pines showed the highest importance value across the chronosequence; with post-fire time, a formation of a sub-canopy of shade-tolerant broad-leaved species and an increase in species richness and diversity was observed. Long periods without fire increased surface fuel loading (66.0 Mg ha-1 ± 5.5 Mg ha-1 for 28 years and 61.5 Mg ha-1 ± 4.6 Mg ha-1 for 60 years-old stands) and changed fire behavior (spread velocity increased from 1.3 m s-1 to 4.1 m s- 1 and flame length from 0.7 m to 1.7 m between the 8 years stands and 28 years - 60 years stands combined). Results suggest that the fire suppression policy in pine forests should be evaluated considering the balance between biological conservation goals and mitigation of high severity fire danger.